Kant e la fenomenologia dell’immaginazione - Feyles, Martino (Aesthetica Preprint, 2023)
In this article, I would like to show that a phenomenological interpretation can shed new light on some of the obscurities present in the Kantian theory of imagination. The interpretation that I will propose does not refer primarily to Heidegger – the author of one of the most discussed readings of the Critique of Pure Reason – but rather to Husserl’s The Phenomenology of Internal Time-Consciousness. I would like to show that, using the Husserlian theory of intuitive acts, it is possible to rethink the distinction between productive and reproductive imagination, accounting for some of the contradictions in the Kantian texts.